Towards and Beyond Edinburgh 2010: A Historical Survey of Ecumenical Missiological Developments since 1910 - Geevarghese, Metropolitan Coorilos (International review of mission, 2010)
This article provides a brief history of mission theology of the global church since Edinburgh 1910, highlighting the seismological shifts and major developments in missiological thinking and praxis over the years and through various world mission conferences, specifically from the perspective of the Commission on World Mission and Evangelism (CWME). It argues that, as we prepare ourselves to celebrate the centenary mission conference in Edinburgh in June 2010, mission theology has moved from its early stage of colonial, Eurocentric expressions to post-colonial and polyphonic articulations of missiology. For the CWME, though, the missiological journey continues even beyond 2010. This article argues that, amongst many important missiological themes that CWME needs to address within the overarching theme of “Ecumenism in Mission”, the themes CWME has identified as its major focus for the coming years – viz. ecclesiology and mission, mission as healing, and mission as contestation – are of crucial pertinence. In the changing global Christian landscape where the centre of gravity of Christianity has moved to the global South, and in a context where new forms of being ecclesial communities are tried out, “The Nature and Mission of the Church” needs to take a “from below” approach, going beyond the traditional frameworks of mainline churches. Mission as healing would provide a comprehensive and more integral perspective to the salvific purpose of God for this world, especially as “healing” is a common strand within many religious, ecclesial and spiritual traditions, offering a dialogical perspective. Mission as contestation is equally significant in today's world where the gospel imperative of confronting satanic forces that express themselves in the form of globalization, neo-imperialism, patriarchy, racism, casteism and eco-violence is of cardinal importance.